Transition to Parenthood - Nazarinia Roy, Roudi. author. aut Link
XIV, 214 p. 3 illus.
Keywords: As couples marry and society evolves, a new generation of families is answering important questions pondered by professionals and couples alike. When should we have children? How many children should we have? What if we can't conceive? When is adoption an option? Can we--should we--fulfill what is expected of us? A comprehensive, multidisciplinary handbook boasting findings across traditional areas of study, Transition to Parenthood brings the contemporary family into clear, useful focus. Its expert coverage tracks current trends in family structures, roles, and dynamics, and explores the impact of individual members and the environment on the family unit. A variety of perspectives (e.g., ecological, life course, TPEX) are presented to best apply to clinical understanding, and the book considers topics as varied as the social class factor in women's fertility, patterns of relationship maintenance, and teaching children about money. And contrary to some schools of thought, the authors argue that macro and micro theories of families must be considered in combination for optimal results. Included in the coverage: A history of fertility in America. The family: diversity and demographics. Childlessness, voluntary and involuntary. The cost of raising a child. Maintaining your relationship across and after the transition to parenthood. Parenting programs and program evaluations. Navigating the transition to parenthood with a child with special needs. Fresh in approach and accessibly written, Transition to Parenthood will be a core reference for a variety of professionals, including family sociologists, family therapists, developmental psychologists, social workers, and counselors.